IMPLEMENTASI CUSTOMER RELATIONSHIP MANAGEMENT DI USAHA MIKRO KECIL DAN MENENGAH BIDANG OTOMOTIF - Manurung, Nicholas Arizona; Nugroho, Agung (Jurnal Terapan Abdimas, 2018)
Abstract. This research discuss the Implementaion of Customer Relationship Management (CRM) strategy in Small and Medium Entreprise ‘Trijaya Ban 83’ workshop that focusing on service repairment industry. The mapping of business condition mention that there is no service differentiation with big and small customer. There are some gap situation in Trijaya Ban 83 workshop such as there is no intense service treatment for customers who generate biggest profit and there is no comprehensive customer database. In this business coaching, coach want to help the business to create a comprehensive Customer Relationship Management Strategy in purpose to increase customer loyalty and keep contributing profit to Trijaya Ban 83 workshop. Methods used in this thesis is qualitative method to gather and analyze customer data of Trijaya Ban 83 workshop in 2016. The result of this research is to create a customer categorization that needs service differently also the implementation to the focus category. The purpose of this Customer Relationship Management implementation is for the workshop to have a systematic selling dan the customer become more loyal in the thight competition of service repairment industry.Keywords: Customer Relationship Management, Automotive Industry, Customer Loyalty, Business Coaching, Small and Medium Entreprises  Abstrak. Penelitian ini membahas mengenai implementasi strategi Customer Relationship Management (CRM) pada Usaha Mikro Kecil dan Menengah / UMKM yang bergerak di bidang jasa bengkel yaitu Trijaya Ban 83. Pemetaan kondisi UKM memperlihatkan bahwa tidak ada perbedaan perlakuan service antara pelanggan besar dan kecil. Beberapa kesenjangan yang terdapat di bengkel Trijaya Ban 83 adalah belum adanya pelayanan lebih terhadap pelanggan yang memberi kontrbusi pendapatan terbesar dan belum ada database konsumen yang lengkap. Oleh karena itu, tujuan dari business coaching ini untuk membantu UKM merumuskan sebuah sistem Customer Relationship Management dengan harapan pelanggan akan semakin loyal dan terus memberikan laba untuk bengkel Trijaya Ban 83. Metode yang digunakan dalam penelitian ini adalah metode kualitatif untuk mengumpulkan dan menganalisis data pelanggan bengkel Trijaya Ban 83 selama tahun 2016. Kesimpulan dari penelitian ini adalah pengelompokan pelanggan fokus yang harus dilayani secara berbeda serta implementasi service yang diberikan kepada kelompok fokus tersebut. Harapan dari implementasi Customer Relationship Management adalah agar bengkel memiliki sistematis penjualan yang teratur dan pelanggan semakin loyal terhadap bengkel dikala kompetisi bengkel semakin ketat. Kata kunci: Customer Relationship Management , Industri Otomotif, Loyalitas Pelanggan, Business Coaching, Usaha Kecil dan Menengah